Pakistan : Third Review Under the Extended Arrangement and Request for Waiver of Nonobservance of Performance Criterion, and Request for Modification of Performance Criteria. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Paper discusses Pakistan's Third Review Under the Extended Arrangement and Request for Waiver of Nonobservance of Performance Criterion (PC).The economy is showing signs of improvement. The FY2013/14 growth projection has been revised upward from 3.1 percent to 3.3 percent, as economic indicators continue to show better-than-expected performance. For FY2014/15, the economy is forecast to expand by about 4 percent. All quantitative PCs were met with the exception of the ceiling on Net Domestic Assets of the State Bank of Pakistan, which was missed by a small margin. On the basis of Pakistan's performance under the extended arrangement, the IMF staff supports the authorities' request for completion of the third review under the arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet